(untitled) (Colloquia Comparativa Litterarum, 2025)
The current text’s purpose is to compare the two novels mentioned in the article’s title, so it could examine some differences and some similarities in creating a fictional world, while emphasizing on the political dimensions of a dystopian narrative. The machine of power is a metaphor used in both novels, which are also comparable in their intention to show general mechanisms that take place within similar political regimes.